2010
DOI: 10.1108/09513541011080002
|View full text |Cite
|
Sign up to set email alerts
|

Which classroom service encounters make students happy or unhappy?

Abstract: PurposeThis paper aims to explore satisfactory and dissatisfactory student‐professor encounters in higher education from a student's perspective. The critical incident technique (CIT) is used to categorise positive and negative student‐professor interactions and to reveal quality dimensions of professors.Design/methodology/approachAn exploratory study using an online application of the well‐established CIT method was conducted. The study took place at a large European university. A total of 96 students took pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 102 publications
(184 reference statements)
3
38
0
1
Order By: Relevance
“…From the viewpoints of Swanson and Davis (2000), and Voss et al (2010), educational services are one of the most intangible, complex, heterogeneous and perishable in nature. Hence such services fall under credence category.…”
Section: Review Of Literaturementioning
confidence: 99%
“…From the viewpoints of Swanson and Davis (2000), and Voss et al (2010), educational services are one of the most intangible, complex, heterogeneous and perishable in nature. Hence such services fall under credence category.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Finally, although online CIT surveys offer accepted ways to collect critical incident data (Voss, Gruber, & Reppel, 2010), researchers cannot follow up with partic ipants to elaborate on a specific encounter or experience. Despite the limitations, the findings provide a rich snapshot of participant satisfaction and dissatisfaction with academic advising at the university level.…”
Section: Limitationsmentioning
confidence: 99%
“…As noted by Voss, Gruber, and Reppel (2010), "the behaviours and attitudes of professors should be the primary determinant of students' perceptions of service quality in higher education" (p. 617). Understanding what our students experience and expect during classroom encounters is needed for professors to provide learning experiences that are both educationally and experientially beneficial.…”
Section: Education As a Servicementioning
confidence: 96%
“…Several researchers have suggested that the examination of student satisfaction in higher education is still underresearched (Appleton-Knapp & Krentler, 2006;Arambewela, Hall, & Zuhair, 2006;Hoffman & Lee, 2014). Voss, Gruber, and Reppel (2010) have specifically called for more research on classroom-based service encounters. While there has been some controversy as to whether education should be treated as a service with students viewed as customers (see, e.g., Bowden, 2011;Clayson & Haley, 2005;Obermiller, Fleenor, & Raven, 2005;Smith, 2013;Svensson & Wood, 2007), student satisfaction, or even delight, can create competitive advantage for the educational institution (Sukwadi, Yang, & Liu, 2011) and positively impact both student motivation (Elliott & Shin, 2002) and learning (Guolla, 1999).…”
Section: A View From the Aisle Revisited: Delight And Outrage In The mentioning
confidence: 99%